Diversity policing-policing diversity: performing ethnicity in police and private-security work in Sweden - Hansen Löfstrand, Cecilia (2014)
This article draws upon two separate studies on policing in Sweden, both investigating "ethnic diversity" as a discourse and a practice in the performance of policing functions: one interview study with minority police officers from a county police authority and one ethnographic study of private security officers. To examine how "diversity policing" and the "policing of diversity" are performed by policing actors, their strategic reliance on an ethnically diverse workforce is examined. The official discourse in both contexts stressed "diversity policing" as a valuable resource for the effective execution of policing tasks and the legitimation of policing functions. There was, however, also another, more unofficial discourse on ethnicity that heavily influenced the policing agents' day-to-day work. The resulting practice of "policing diversity" involved situated activities on the ground through which "foreign elements" in the population were policed using ethnicized stereotypes. Div